Peningkatan Hasil Belajar Praktikum Fisika dengan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) - Epi Yarlis (Journal of Education and Culture (JEC), 2022)
This classroom action research was conducted with the aim of knowing the improvement of students' physics practicum learning outcomes on light wave material using the Team Assisted Individualization (TAI) type of cooperative learning model. The research subjects were students of class XI IPA.6 MAN 2 Kota Padang in the 2020/2021 academic year. The research was carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. Cycle I was carried out on the practical material of parallel plan glass refraction and the second cycle on the practical material of the diffraction grating. Students' practicum activity data is extracted with Student Activity Observation Sheets, teacher practicum learning management data is extracted with Learning Management Observation Sheets, while students' practicum learning outcomes data are excavated using Formative Tests in the form of practice. The results showed that: (1) Cycle I involving students with high initial abilities obtained an average learning outcome of 78.56 and a percentage of completeness 41%; (2) Cycle II involving students with high initial abilities and being given material and skill reinforcement obtained an average learning outcome of 87.78 and a 95% completeness percentage; (3) The learning outcomes of students' physics practicum in the second cycle have increased from the first cycle, both on average and the percentage of completeness. In conclusion, the Team Assisted Individualization (TAI) learning model can improve students' physics practicum learning outcomes.